WIRE-ARC ADDITIVE MANUFACTURING: RECENT DEVELOPMENTS AND POTENTIAL - Doncheva, Elisaveta; Krstevska, Aleksandra; Djidrov, Marjan; Zdraveski, Filip; Velkovski, Trajche (The Academy of Applied Technical Studies Belgrad, 2023)
Wire-arc additive manufacturing (WAAM) is a promising technology for producing medium and large components without traditional subtracting technologies. It is a hybrid of two manufacturing techniques: additive manufacturing and welding. The use of this technology has grown significantly due to advantages such as material and energy savings while achieving high deposition rates and low cost. However, there are some issues with microstructure homogeneity, and properties are affected due to the complexity of the arc-induced thermal cycles and metallurgical mechanisms, resulting in high residual stresses, distortion, porosity, cracks, and delamination. This article summarises the progress made in the field of wire additive manufacturing, with a focus on welding systems, tool path design software, material analysis, and control systems. It also highlights some critical aspects that must be addressed to ensure high-quality production, such as control and diagnosis mechanisms for defect monitoring, the effects of parameters and their optimisation possibilities for improving quality, ensuring process stability, and possible post-deposition heat treatments. The conclusions suggest further improvements to the wire-additive manufacturing process in terms of accuracy, reliability, and efficacy, as well as future applications of the technology and research activities.
Keywords: Additive manufacturing; WAAM; welding; Mechanical properties; Monitoring system